The Psychometric Properties of Attentional Control Scale and Its Relationship with Symptoms of Anxiety and Depression: A Study on Iranian Population - Imaneh Abasi; Parvaneh Mohammadkhani; Abbas Pourshahbaz; Behrouz Dolatshahi (Iranian Journal of Psychiatry, 2017)
Objectives: The attentional control scale is a self- report questionnaire that assesses individual differences in attentional control. Despite its extensive use, the psychometric properties of the Persian version of the ACS are not well understood. Thus, the present study aimed at investigating the psychometric properties of the attentional control scale and its relationship with symptoms of anxiety and depression in Iranian population.